Pengenalan Huruf Abjad Pada Anak Taman Kanak-kanak Melalui Quizizz di TK Islam Wahyu Bhakti - Anggun Citra Dini Dwi Puspitasari; Zetty Karyati (Peneliti.net, 2021)
This research aims to determine the use of Quizizz in learning to recognize letters of the alphabet to kindergarten’s children in Wahyu Bhakti Islamic Kindergarten. The method used in this research is descriptive with a qualitative approach. The results found in this research indicate that Quizizz can provide convenience for teachers to carry out learning to recognize letters of the alphabet to kindergarten’s children during a pandemic like today. In addition, Quizizz can also make it easy for children to recognize the shapes of the letters of the alphabet.